Table of Content - - (Journal of Islamic Sciences, 2024)
Table of Content: 1. Family Alienation And The Challenges Of The Technological Age Amirah Mohammad Alajmi 2. Controls and provisions of electronic financial papers (a comparative jurisprudential study) Mohammed Khalil Mohammed Alshaikhi 3. The Abrogation Issue in Verses of Night Prayer: Applied Study Hanin Khalaf Al-Mawadiya 4. The Islamic jurisprudence of the Prophet Mohammed in crisis management Noureddine Abdelati Kailan